2019
DOI: 10.1088/1475-7516/2019/10/009
|View full text |Cite
|
Sign up to set email alerts
|

de Sitter, α′-corrections & duality invariant cosmology

Abstract: Demanding O(d, d)-duality covariance, Hohm and Zwiebach have written down the action for the most general cosmology involving the metric, b-field and dilaton, to all orders in α in the string frame. Remarkably, for an FRW metric-dilaton ansatz the equations of motion turn out to be quite simple, except for the presence of an unknown function of a single variable. If this unknown function satisfies some simple properties, it allows de Sitter solutions in the string frame. In this note, we write down the Einstei… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

3
20
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 27 publications
(23 citation statements)
references
References 36 publications
3
20
0
Order By: Relevance
“…It was shown in [35,30] that under some assumptions on the function F (H) there are de Sitter solutions to the equations (21), and that we can construct perturbative solutions by solving the equations order by order 3 . Conditions for having a de Sitter solution in the Einstein frame were studied in [38]. Furthermore, in [39] Anti-de Sitter solutions for the bosonic case were explored, and in [40,41] non-singular solutions were discussed.…”
Section: Lowest Order Vacuum Action and α -Correctionsmentioning
confidence: 99%
“…It was shown in [35,30] that under some assumptions on the function F (H) there are de Sitter solutions to the equations (21), and that we can construct perturbative solutions by solving the equations order by order 3 . Conditions for having a de Sitter solution in the Einstein frame were studied in [38]. Furthermore, in [39] Anti-de Sitter solutions for the bosonic case were explored, and in [40,41] non-singular solutions were discussed.…”
Section: Lowest Order Vacuum Action and α -Correctionsmentioning
confidence: 99%
“…This remarkable result leads them to show that, in bosonic string theory, non-perturbative de-Sitter (dS) vacua are admitted by including complete α ′ corrections. In [21], the analogy in the Einstein frame is then discussed. In our recent work [22], we showed that similar stories occur for configurations depending on a single space coordinate, and non-perturbative Anti-de-Sitter (AdS) vacua are also allowed.…”
Section: Jhep01(2020)164mentioning
confidence: 99%
“…They subsequently proved that non-perturbative de-Sitter (dS) vacua are possible in bosonic string theory. The analogy in the Einstein frame is then studied in [24].…”
Section: Introductionmentioning
confidence: 99%